Gut bacteria facilitate leaf beetles in adapting to dietary specialization by enhancing larval fitness - Meiqi Ma; Jing Luo; Xiaotong Chen; Chong Li; Siqun Li; Jianghua Sun; Letian Xu (npj Biofilms and Microbiomes)
Abstract Dietary specialization between insect stages can reduce intraspecific food competition. The involvement of gut bacteria and the mechanisms underlying this phenomenon received limited attention. Plagiodera versicolora is a pest harming Salicaceae trees. Here, we confirmed dietary specialization in P. versicolora, wherein adults prefer new leaves, while larvae predominantly consume mature leaves when both types are available. We demonstrated the larval preference for mature leaves confers ecological advantages by promoting growth, development and immunity and this advantage is contingent upon the presence of gut bacteria. Gut microbiota in larvae revealed a significant enrichment of Pantoea when feeding new leaves, with P. anthophila exhibiting the most pronounced inhibitory effect on larval development. Further exploration identified specific metabolites, such as Tyrosyl-valine, with higher content in new leaves, which serve as substrates for the entomopathogenic gut bacterium to facilitate its proliferation. This study provides a fresh perspective on the ecological role of gut bacteria.